Efficiency enhancement mechanisms and performance of SiCf/SiC composites under ultrasonic vibration-assisted milling with liquid nitrogen cooling - Dengzhou Hu; Guofu Ding; Lei Jiang; Jinxuan Bai; Xin He (Materials Research Express)
Ultrasonic vibration cutting technology has made remarkable progress in the application of hard and brittle materials, but there are still some challenges in aerospace silicon carbide fiber toughened silicon carbide ceramic matrix composite (SiCf/SiC) processing. This study systematically investigates the synergistic mechanisms and machining performance effects of liquid nitrogen cooling combined with ultrasonic vibration-assisted milling on silicon carbide fiber-reinforced silicon carbide (SiCf/SiC) ceramic matrix composites. The results demonstrate that the liquid nitrogen-cooled ultrasonic vibration-assisted machining technique exhibits significant advantages in improving cutting performance, surface quality, and tool life extension. Specifically, compared with conventional cutting (dry cutting) and ultrasonic vibration cutting, the main cutting force in ultrasonic-assisted cutting under a liquid nitrogen cooling environment is reduced by approximately 77.5% and 25% and the feed force is reduced by approximately 48.8% and 24.97%, the tool life is extended by about 157.9% and 25% respectively, and the surface roughness can be reduced by nearly 68.1% and 19.6%.The reduction in cutting force under ultrasonic vibration is primarily attributed to the periodic contact and separation between the workpiece and the tool, which improves the heat dissipation in the cutting area, lowering the cutting temperature and consequently reducing the frictional force and extrusion force between the tool and the workpiece. Additionally, the rapid cooling of the cutting zone by liquid nitrogen at the moment of tool-workpiece separation increases the brittleness of the materials in high-temperature areas and the deep cooling layer produces smaller micro cracks under high-frequency vibrations, promoting microbrittle removal, which can further reduce cutting force and improve machined surface quality while extending tool life. This study offers a new solution for the efficient cutting of such difficult-to-machine materials, particularly with broad application prospects in the aerospace field.